TRENDS IN THE YIELDS OF MAJOR EXPLOITED FISHERIES OF THE EAST COAST OF INDIA - Dharmaraja, S K; Philippose, Varughese (Indian Journal of Fisheries, 2011)
On the west coast of India the bulk of the landings comprise of four major fisheries namely oil sardine, mackerel, Bconbay duck and penaeid and nonpenaeid prawns. But these four category of fishes form very minor fishery on the east coast of India. However, elasmobranchs, cat fi^es, ’other sardines’,*’ anchovies and white baits, ’other clupeids’,** sciaenids, ribbon fish, silverbellies and penaeid prawns which constitute the bulk of the total catch of die east coast form the nine major fisheries of this coast